COMBINED ENTEROSORBATE IN COMPLEX TREATMENT OF ATOPIC DERMATITIS IN CHILDREN - A.A. Alekseeva ("Paediatrician" Publishers LLC, 2011)
The article presents a review of studies of prebiotic Lactofiltrum efficacy in complex treatment of atopic dermatitis (AD) in children. AD takes significant place in the structure of allergic diseases in children. 70-80% of patients with AD have intestinal dysbiosis resulting in disorder of barrier function of intestine. Protocols of AD treatment of children include not only elimination diet, antihistamine drugs, topical treatment but enterosorbates. Drugs based on hydrolyzed lignin are actively used during recent years. One of these drugs is prebiotic with sorbent effect Lactofiltrum.Key words: children, atopic dermatitis, enterosorbates, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 180-183)